Development of a data manager support manual for hematopoietic cell transplantation and cellular therapy for Latin America: an innovative approach to data reporting to the Center for International Blood & Marrow Transplant Research - Costa, Flavia Ferreira da; Sabaini, Paula Moreira da Silva; Silva, Cinthya Muniz Corrêa Rocha da; Simeone, Anderson João; Neves, Heliz Regina Alves das; Ammi, Monique; Concilio, Rosana Rocha Batista; Vigorito, Afonso Celso; Miranda, Eliana Cristina Martins; Otuyama, Leonardo Jun; Santos, Joaquim Gasparini dos; Toledo, Mariza; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
The Brazilian Hematopoietic Cell Transplantation and Cellular Therapy (HCT-CT/BR) Registry depends on data manager (DM) training to ensure sustainability, for which it is essential to standardize processes. The objectives of this study were to describe the development of a support manual for Brazilian DMs reporting to the Center for International Blood and Marrow Transplant Research and to present quality assessment results. The descriptive study (Feb–Aug 2024) included structuring, content creation, and dissemination of the manual. Survey assessed satisfaction. The manual was launched at the XXVIII Brazilian Society of Cellular Therapy and Bone Marrow Transplantation Congress. Thirty-nine professionals rated it 9.3/10 for satisfaction and 9.4/10 for recommendation. A manual is crucial for standardizing processes and ensuring data quality, offering clear and up-to-date guidance.